Impact of the different casing material on the yield of Calocybe indica in polyethylene bag and bed system - Nath, Manoj; Barh, Anupam; Sharma, Annu; Bijla, Shweta; Bairwa, Rakesh Kumar; Kamal, Shwet; Sharma, VP (Mushroom Research, 2022)
Calocybe indica is well known for its nutritional value, longer shelf life and ability to grow in warm humid climatic conditions. Casing material plays an important role in its cultivation and yield determination. The present study explored the impact of the different casing material on the biological efficiency (BE) of the Calocybe indica. Here, we have used eight types of casing material sterilized thorough formalin, tunnel pasteurization and autoclave method in the poly-ethylene (PE) bag system. Highest and significantly similar BE was observed in the garden soil +sand (75:25) casing material prepared by tunnel pasteurization, autoclave, formalin method and formalin treated - Farmyard manure (FYM) + sand (75:25) casing material (54.3-56.3%). The lowest BE was observed in the coir pith casing material (32.3%). As utilization of the polyethylene bag is not environment friendly, therefore this study also explored the cultivation of the C. indica in the bed system with two types of casing material prepared through tunnel pasteurization method. The significantly similar BE was observed in the FYM+ coir pith (80:20) and garden soil+ sand (75:25) casing material in the bed system. In addition, without casing analysis revealed mass pinning and inability of the fruit body maturation in PE bag system. In bed system, the fruit body was matured with curved stipe and yielded (BE-28.5%) in absence of casing.